Pengaruh Rasio Profitabilitas, Leverage dan Aktivitas Terhadap Pertumbuhan Laba pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019-2021 - Sari Faturrohma; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2023)
This study aims to examine the effect of profitability ratios, leverage ratios, and activity ratios on profit growth. Profitability is measured by return on assets, leverage is measured by debt to equity ratio, while activity is measured by total asset turnover. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Sampling was carried out using purposive sampling method. The number of samples in this study were 12 food and beverage companies with 36 observations obtained. The analytical method used is multiple linear regression analysis. The results showed that the profitability ratio has a positive effect on profit growth, the leverage ratio has a positive effect on profit growth, the activity ratio has no effect on profit growth. Taken together the ratio of profitability, leverage and activity affect profit growth.Keyword: Profitability, leverage, activity, profit growth